Implementation of Character Education as the Basis of National Insights for PPKN Students of Universitas Labuhanbatu - Sri Wahyuna Rambe; Junita Junita (Budapest International Research and Critics University, 2022)
This study aims to find out the implementation of character education as the basis for the National Insight of PPKN students at Labuhanbatu University and to find out the strengthening of character education as the basis for national insight for PPKN students at Labuhanbatu University. The focus of research is more directed at character education as the foundation of national insight. Research Using Qualitative Descriptive Approach. The key informants for this research are respondents as a sample of 74 students. This Research Has Been Implemented At Labuhanbatu University. The instrument in this study was to collect data using observation and questionnaire methods. Research uses techniques to analyze data, namely data reduction techniques, data presentation, and conclusion drawing. Results of Research on Implementation of Character Education Implementation as the Foundation for National Insights for Ppkn Students at Labuhanbatu University There are still characters that can strengthen the formation of good national insights. However, there are some students who don't care about these characters. Such as, lack of knowledge about the history of the Indonesian struggle, such as the names of heroes who have fallen to fight for Indonesian independence, and other heroes' days. So where lies the sense of national spirit, and love for the homeland, towards the student himself. How National Insight Can Be Perfectly Achieved If The Character / Attitude That Is In The Students Still Can't Develop / Implemented Well. Therefore, it is necessary to apply character education as the basis for the best national insight.